2011
DOI: 10.3324/haematol.2011.043372
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide, thalidomide, and dexamethasone as induction therapy for newly diagnosed multiple myeloma patients destined for autologous stem-cell transplantation: MRC Myeloma IX randomized trial results

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThalidomide is active in multiple myeloma and is associated with minimal myelosuppression, making it a good candidate for induction therapy prior to high-dose therapy with autologous stem-cell transplantation. Design and MethodsOral cyclophosphamide, thalidomide, and dexamethasone was compared with infusional cyclophosphamide, vincristine, doxorubicin, and dexamethasone in patients with newly diagnosed multiple myeloma. ResultsThe post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
114
3
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 33 publications
7
114
3
3
Order By: Relevance
“…The benefit conferred by thalidomide combinations in induction was confirmed by the Myeloma IX and Total Therapy 2 trials (Morgan et al, 2012;Barlogie et al, 2006b). The IFM 2005-01 trial demonstrated that bortezomib and dexamethasone was also superior to VAD, increasing the pre-ASCT response rate to 79% from 63%, (Harousseau et al, 2010), and a similar improvement with bortezomib-based induction was observed in the HOVON65/GMMGHD4 trial (Sonneveld et al, 2012).…”
Section: Novel Agent Inductionmentioning
confidence: 89%
“…The benefit conferred by thalidomide combinations in induction was confirmed by the Myeloma IX and Total Therapy 2 trials (Morgan et al, 2012;Barlogie et al, 2006b). The IFM 2005-01 trial demonstrated that bortezomib and dexamethasone was also superior to VAD, increasing the pre-ASCT response rate to 79% from 63%, (Harousseau et al, 2010), and a similar improvement with bortezomib-based induction was observed in the HOVON65/GMMGHD4 trial (Sonneveld et al, 2012).…”
Section: Novel Agent Inductionmentioning
confidence: 89%
“…Better results were achieved with three-drug combinations including thalidomide or bortezomib plus conventional chemotherapeutic agents, such as doxorubicin and cyclophosphamide (13,19,20).…”
Section: Induction Regimensmentioning
confidence: 99%
“…Similarly, bortezomib plus dexamethasone (VD) showed an ORR of 78% in comparison with 63% with VAD (P<0.001) (16). Two randomized phase III trials evaluated a short course of lenalidomide and dexamethasone (Rd) as induction before ASCT, showing an ORR of 76%, including 29% of patients achieving at least a VGPR (17,18).Better results were achieved with three-drug combinations including thalidomide or bortezomib plus conventional chemotherapeutic agents, such as doxorubicin and cyclophosphamide (13,19,20).A significant improvement in ORR in comparison with VAD was reported with doxorubicin in combination with thalidomide-dexamethasone (TAD) (88% vs 79%, P=0.005) (19) and doxorubicin in combination with bortezomib and dexamethasone (PAD) (78% vs 54%, P<0.001) (13).Cyclophosphamide in combination with thalidomide-dexamethasone (CTD) significantly enhanced the ORR in comparison with cyclophosphamide-VAD (83% vs 71%, P<0.0001) (20).The three-drug combination bortezomib-thalidomide-dexamethasone (VTD) was compared with TD and multi-agent chemotherapy (21,22). A significant improvement in the CR rate was detected with VTD compared with TD (35% vs 14%, P=0.0001) and with multi-agent chemotherapy (35% vs 21%, P=0.01) (21).…”
mentioning
confidence: 99%
“…It should be noted that LEN and THAL are not currently approved for use as frontline therapy under the Japanese medical insurance system. Data from phase III studies describing outcomes in response to regimens containing novel agents are summarized in Table 2 [5][6][7][8][9][10][11][12][13].…”
Section: Induction Therapy In Patients Eligible For Autologous Stem Cmentioning
confidence: 99%